Pengaruh Tingkat Kebisingan Terhadap Daya Ingat Mahasiswa - Izzatul Ummah; Shafira Putri Charnita; Tsamarah Rifqah Q.A; Siti Rahmah (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to explore the effect of noise intensity on students' college memory. The research hypothesis is that noise affects the ability to remember. The study involved 16 Psychology students from Syiah Kuala University, divided into two groups: an experimental group (noisy conditions) and a control group (quiet conditions). The research methodology used an experimental design with a between-group technique, providing both pretests and posttests in the form of word memorization for each group. Data analysis was conducted using Wilcoxon and Mann-Whitney tests. The results showed that the posttest scores of the experimental group significantly decreased after being exposed to noise, while the scores of the control group remained relatively stable. The hypothesis test results indicated p0.001, suggesting a significant effect of noise levels on memory in both the control and experimental groups. These findings highlight the importance of a conducive learning environment for effective learning processes.